Rapid decolorization of textile wastewater by green synthesized iron nanoparticles - ERKEN, ESRA; YÜCESOY ÖZKAN, ZEYNEP (IWA PUBLISHING, 2018)
The effectiveness of green tea (Camellia sinensis) and pomegranate (Punica granatum) extracts for the production of iron nanoparticles and their application for color removal from a textile industry wastewater was investigated. Polyphenols in extracts act as reducing agents for iron ions in aqueous solutions, forming iron nanoparticles. Pomegranate extract was found to have almost a 10-fold higher polyphenolic content than the same amount of green tea extract on a mass basis. However, the size of the synthesized nanoparticles did not show a correlation with the polyphenolic content. 100 ppm and 300 ppm of iron nanoparticles were evaluated in terms of color removal efficiency from a real textile wastewater sample. 300 ppm of pomegranate nanoscale zero-valent iron particles showed more than 95% color removal and almost 80% dissolved organic carbon removal. The degradation mechanisms are is considered to be adsorption and precipitation to a major extent, and mineralization to a minor extent.
Keywords: green synthesis; green tea (Camellia sinensis); iron nanoparticle; pomegranate (Punica granatum); textile wastewater; ZERO-VALENT IRON; ANTIOXIDANT ACTIVITY; PHENOLIC COMPOSITION; POMEGRANATE JUICE; DEGRADATION; FENTON; POLYPHENOLS; OXIDATION; EXTRACTS